A critical vidl of the jury system in west Malaysia / Azlan Abd. Aziz - Abd. Aziz, Azlan (Faculty of Law, 1986)
In this chapter, it is necessary to consider the introduction of the system of trial by jury in West Malaysia by the British. To further understand the development of the system of trial by jury, one has to trace Its history through the following events, that Is, the colonisation of each state in Vest Malaysia. Trial by jury in Vest Malaysia was introduced by the British through the First Charter of Justice in 1807. The Charter was only introduced in Penang which has the distinction of being the first Malaysian state to be bestowed with the system of trial by jury. Trial by jury was then extended to Malacca and Singapore by the introduction of the Second Charter of Justice in 1826.